2014
DOI: 10.1002/aic.14370
|View full text |Cite
|
Sign up to set email alerts
|

Rheological predictions of network systems swollen with entangled solvent

Abstract: The mechanical properties of a cross-linked polydimethylsiloxane (PDMS) network swollen with nonreactive entangled PDMS solvent was previously studied experimentally. In this article, we use the discrete slip-link model to predict its linear and nonlinear rheology. Model parameters are obtained from the dynamic modulus data of pure solvent. Network rheology predictions also require an estimate of the fraction and architecture of dangling or inactive strands in the network, which is not directly measurable. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…An unknown fraction of network imperfections allowed only qualitative agreement with experimental observations. Katzarova et al (2014) were able to estimate composition and predict nonlinear rheology of swollen network using DSM. Andreev et al (2013) showed that the DSM can be applied without any adjustments to shear flow and yield agreement over a wide range of deformation rates, while agreement with elongational flow data at large strains remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…An unknown fraction of network imperfections allowed only qualitative agreement with experimental observations. Katzarova et al (2014) were able to estimate composition and predict nonlinear rheology of swollen network using DSM. Andreev et al (2013) showed that the DSM can be applied without any adjustments to shear flow and yield agreement over a wide range of deformation rates, while agreement with elongational flow data at large strains remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, they either i) directly sample an ensemble of n c polymers from the target MWD (the subscript "c" stands for chains), [14][15][16][17] or ii) consider a BMF with n f fractions that is derived from the MWD. [18][19][20][21] In the limit of large n c or n f , both approximations converge to the expected polydisperse behavior.…”
Section: Polydispersity In Molecular Simulationsmentioning
confidence: 64%
“…Popular implementations of the TM deal with polydispersity by creating an ensemble of chains from the MWD [37][38][39]. The same approach can be employed with multi-chain SLMs, although it is less common due to increased computational cost [26,[40][41][42]. Recent work on discretizing nearly monodisperse MWD (polydispersity index 1.1) recommends using a "blend of monodisperse fractions" of f = 5 − 10 suitably selected chain lengths [43].…”
Section: The Problem With Polydispersitymentioning
confidence: 99%